Evolving meaning: using genetic programming to learn similarity perspectives for mining biomedical data - Sousa, Rita Isabel Torres de (2019)
Tese de mestrado, Bioinformática e Biologia Computacional, Universidade de Lisboa, Faculdade de Ciências, 2019